2012
DOI: 10.1007/978-3-642-32060-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Towards Robust Mobility, Flexible Object Manipulation, and Intuitive Multimodal Interaction for Domestic Service Robots

Abstract: Abstract. In this paper, we detail the contributions of our team NimbRo to the RoboCup @Home league in 2011. We explain design and rationale of our domestic service robot Cosero that we used for the first time in a competition in 2011. We demonstrated novel capabilities in the league such as real-time table-top segmentation, flexible grasp planning, and real-time tracking of objects. We also describe our approaches to humanrobot cooperative manipulation and 3D navigation. Finally, we report on the use of our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In this context, some competitions including real-world human-robot interaction must be effective for facilitating researchers to study embodied cognitive systems and emergent symbol systems, and for evaluate appropriateness of the developed systems. RoboCup@Home is an obvious candidate [162][163][164][165].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some competitions including real-world human-robot interaction must be effective for facilitating researchers to study embodied cognitive systems and emergent symbol systems, and for evaluate appropriateness of the developed systems. RoboCup@Home is an obvious candidate [162][163][164][165].…”
Section: Discussionmentioning
confidence: 99%
“…Among others, they successfully demonstrated real-time 3D object recognition and tracking for physical human-robot-interaction [50], tool use [51], and recently non-rigid object recognition and tracking for skill transfers [51].…”
Section: Object Recognitionmentioning
confidence: 99%
“…Some teams report using a combination of grasp/motion planning and parameterized motion primitives for particular manipulation tasks [51,58], allowing for complex grasping in complex scenes. For the control of arm and body motions, an approach has been successfully demonstrated that is compliant in task space [50]. It enables many important robot capabilities, such as opening refrigerators, cupboards and drawers or cooperatively carrying a table with a human.…”
Section: Object Manipulationmentioning
confidence: 99%
“…Some works, e.g., [8] and [9], have explored planning in 3D representations of environment maps leading to much robust navigation that could inherently account for the robot's full height and complete traversability in the environment.…”
Section: Related Workmentioning
confidence: 99%